Casos y cosas: semanario popular (Vol. 1, No. 36) - Imprenta La Region (My University, 1920)
SPANISH: Incluye: Bombos y palos, otra infamia del prefecto, ¡Esos muchachos!, Rincón femenino, La región.

ENGLISH: Bombs and sticks, another infamy of the prefect, those boys, women's corner, the regions.
Cases and things: popular weekly (Vol. 1, No. 36)
Keywords: Periodicals; Satire, Peruvian; Humor; Iquitos (Perú)--revistas; Perú--revistas satíricas